Atypical Presentation of Constrictive Pericarditis in a Holstein Heifer - Mohamed M. Elhanafy; Dennis D. French (Case Reports in Veterinary Medicine)
The field diagnosis of constrictive pericardial effusion is often established on the pertinent pathognomonic physical examination findings, but the condition cannot be ruled out based on absence of these cardinal signs. Constrictive pericardial effusion is not always manifested by bilateral jugular venous distention and pulsation, brisket edema, and muffled heart sounds, all of which are considered the key points in the field diagnosis of pericardial effusion and hardware disease. This case will also document that the outcomes of hematology, serum biochemistry panels, and blood gas analysis can be totally inconsistent with passive venous congestion and constrictive pericardial effusion in cattle. Chest radiographic findings revealed radio dense, wire-like objects; the findings were suggestive but not conclusive for pericardial or pleural effusions, due to indistinguishable diaphragmatic outline and cardiopulmonary silhouette. Cardiac ultrasonography was found to be an excellent paraclinical diagnostic procedure for cases that potentially have traumatic pericarditis and constrictive pericardial effusion. Ultrasound-guided pericardiocentesis was also a valuable diagnostic aid in establishing a definitive diagnosis.